DAMPAK PENDIDIKAN AGAMA ISLAM TERHADAP PEMBENTUKAN KEPRIBADIAN ANAK - Bahar (Musawa: Journal for Gender Studies, 2021)
Islamic education is physical and spiritual guidance based on Islamic laws to form main personality according to Islamic standards. In other words, the main personality is the Muslim personality, that is the personality who has Islamic religious values, chooses and decides and acts based on Islamic norms, and is responsible in accordance with Islamic values. The general indicator of an ideal personality of a child is to always pay attention to his/her behavior in worship, traditional behavior, destructive behavior, and constructive behavior. Behavior in worship, for example carrying out prayers perfectly, both in terms of pillars and conditions, doing remembrance and praise of Allah (dhikr) and wirid after prayer, as well as completing the sunnah rawatib prayers. Traditional behavior, for example in ethics of eating, is preceded by praying, eat with the right hand, social and friendly etiquette, travel etiquette, and so on. Destructive behavior, for example avoiding the dangers of lust, the dangers of wealth and being stingy, disdainful and showing off, being arrogant, boasting, cheating, and so on. The constructive behavior, for instance always do self-reflection and self-introspection, tafakkur,etc.